States of exception in American history - Gerstle, Gary, 1954-; Isaac, Joel, 1978- (Chicago : The University of Chicago Press, 2021)
This text brings to light the remarkable number of instances since the Founding in which the protections of the Constitution have been overridden, held in abeyance, or deliberately weakened for certain members of the polity. In the United States, derogations from the rule of law seem to have been a feature of - not a bug in - the constitutional system. A comprehensive account of the politics of exceptions and emergencies in the history of the United States, this book weaves together historical studies of moments and spaces of exception with conceptual analyses of emergency, the state of exception, sovereignty, and dictatorship.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 6, 2021).
Keywords: War and emergency powers -- United States -- History; Crises -- Political aspects -- United States -- History; United States -- Politics and government -- History; Law; Laws of specific jurisdictions & specific areas of law